TRACING THE PATRIOTIC STREAKS AMONG THE NATIONAL ANTHEM OF PAKISTAN AND TURKEY: A DEPICTION OF NATIONALISM - Sarfraz, Rida; Ashfaq, Naheed; Abid, Faiza; Riaz, Sadia; Niazi, Aisha (International Journal of Psychosocial Rehabilitation, 2020)
The national anthem is always sung at the learning institutions or during the country’s special occasions. Various countries regard their national anthem as the back bone of patriotism and expression of their strength of national identity. National anthem reveals entities that have a special noble role to play in the country’s prosperity. This paper will probe the highly defined patriotic streaks among the national anthem of two Muslim countries that are Pakistan and Turkey. Due to the enriched heritage and significant historical affiliation of both aforementioned countries, their respective national anthem is specifically portraying the various aspects exhibited via the mode of language. Furthermore; the paper will explore the linguistic aspects as well as pragmatic paradigms to peel out the layers of the meaning mentioned in these anthems. For the analysis of these anthems, an analytical framework was formulated and used which has been adapted from So (2005). It also incorporates both contextual and linguistic analyses of the text under discussion. Moreover, it will look for the notion of metafunctions of language (Halliday&Hasan, 1989), in order to examine relation between language use and context of situation. This framework will help us to determine many dimensions like nationalism, patriotism, refuge, faith, determination, wishes etc which draws us towards the exactness of the meaning of the national anthems of both countries